Knowledge, experiences, and practices on safe opioid use in patients recently discharged from hospitals in Western Nepal: a qualitative study - Adhikari, Sundar; Gurung, Roshani; Shrestha, Shakti; Alrasheedy, Alian A.; Paudyal, Vibhu; Lamshal, Ramesh; Sharma, Pratima; KC, Bhuvan (Frontiers in Pharmacology, 2025)
BackgroundRational prescribing and use of opioids is key to managing pain and mitigating adverse effects. Limited research exists on patient’s knowledge and experiences regarding use of prescribed opioid use within low resource settings.ObjectivesThis study aimed to explore the knowledge, experiences, and practices related to opioid use among patients discharged from hospitals in Western Nepal.MethodsA qualitative study was undertaken involving semi-structured interviews with patients discharged from a tertiary hospital in Western Nepal who had been prescribed opioids for pain management. Thematic analysis was used to identify key themes related to opioid use, counseling practices, and knowledge gaps.ResultsA total of 30 patients were interviewed. Analysis showed five themes viz. awareness of purpose, effectiveness and adverse effects, patient experience with opioid therapy, adherence to administration instruction and storage practices, risk awareness and safety practices, and follow-up and continuity of care. Participants showed awareness of opioid dosage, frequency, and storage but lacked knowledge of adverse effects, dependence, and tapering. Counselling from healthcare providers was noted but was often limited and inconsistent in regard to adverse effects and the long-term risks. None of the participants reported having a shared plan of action including follow up post-discharge.ConclusionThere are critical gaps in patient education and discharge counselling regarding opioid use in Nepal. Strengthening pharmacist-led counselling, implementing structured discharge protocols, and developing tailored educational interventions are essential to promote safe opioid use and reduce misuse in low resource settings.